G36 Palliative Care in Neonates with Antenatally and Postnatally Diagnosed Congenital Heart Disease. (4th June 2013) - Campbell, J; Harris, S; Yates, R; Kelsall, W
Abstract : Introduction: The RCPCH 1 and BAPM 2 have issued guidance on palliative care for neonates with life limiting conditions. There is no reference to congenital heart disease (CHD). Methods: We reviewed 7 babies with CHD born between March 2010 and December 2012 who received palliative care. Results: Seven babies were identified with a median birthweight of 2690g (1740–3900g) and gestation 40 weeks (35+3–42+0). Five had antenatally detected complex CHD which was confirmed postnatally. In 3 cases palliative care plans were made antenatally and these babies did not receive any medical intervention. Two were discharged and died at home in the community at 3 days of age with support from their general practitioner and the hospice (True Colours Team). One died in hospital at 7 days in accordance with the parents' wishes. For two babies there were antenatal discussions but no agreed postnatal plans made. One had an umbilical line for a prostaglandin infusion until the decision was made for palliative care at six days of age. She died at home at sixteen days with support. Another baby with antenatally diagnosed severe tetralogy of Fallot with absent pulmonary valve was admitted to NICU. On day three she collapsed and required ventilation and inotropes. After careful discussion intensive care was withdrawn on day 4 and she died in hospital later that day. Two babies were diagnosed with CHD postnatally. One had a 6mm atrial septal defect as part of Smith-Lemli-Opitz (SLO) Syndrome. After confirmation of the diagnosis of complex SLO, palliative care was instigated. She was discharged home at 10 weeks and died at home at 14 weeks of age. A baby with a large VSD had trisomy 18 confirmed on day 8 and the decision for palliative care was made the following day. She died at home aged 21 months. Conclusion: This case series shows that the local end of life care pathway, introduced in 2011, is effective for complex CHD. Multi-professional hospital and hospice teams have learnt important lessons, including: supply pain relieving medications at discharge, early involvement of the GP and the importance of an ongoing lead paediatric consultant overseeing care. References: Witholding or Withdrawing Life Sustaining Treatment. Royal College of Paediatrics and Child Health. May 2004. Palliative Care (Supportive and End of Life Care) A Framework for Clinical Practice in Perinatal Medicine. British Association of Perinatal Medicine. August 2010. Acknowledgement: East Anglia's Children's Hospices (EACH) True Colours Symptom Management Team.